Diagnostic study of the transformation of educational internships in three public Islamic Universities in Indonesia - Ansyah, Edi; Salamah, Salamah; Rahman, Alvin Yanuar; Rahmat, Azwar (International research journal of management, IT and social sciences, 2024)
This study aims to diagnose the transformation of educational internship programs in three State Islamic Universities (UIN), namely UIN Fatmawati Sukarno Bengkulu, UIN Syarif Hidayatullah Jakarta, and UIN Sunan Gunung Djati Bandung. The main focus of the research is to understand the changes that occur in the implementation of educational internships, the supporting and inhibiting factors of transformation, as well as the impact on students and institutions. The research method used was a diagnostic study with a qualitative approach. Data were collected through in-depth interviews, observations, and document analysis related to the internship program. The results showed that the transformation of the educational internship program involved significant changes in the curriculum, increased student involvement, and the use of technology in teaching. The main supporting factors include Merdeka Belajar-Kampus Merdeka policy support, supporting technology, and university commitment while inhibiting factors include variations in the quality of partner schools, limited technological infrastructure, and curriculum adjustment constraints. This transformation has a positive impact on improving students’ teaching skills, better work readiness, and strengthening the university’s academic reputation.